Rozwiąż i sprawdź równania: a) 8(2 x - 1) + 3(4 - 5x) = 0 b) 2(7x - 3) = 5 - 4(6 - 4x)​

Odpowiedź :

Odpowiedź:

a)  0,8(2x-1)+0,3(4-5x)=0

1,6x-0,8+1,2-1,5x=0

0,1x+0,4=0

0,1x=-0,4   |*10

x=-4

b) 2(7x-3)=5-4(6-4x)

14x - 6 = 5 - 24 + 16x

14x - 16x = 5- 24 +6

-2x = -13 /:(-2)

x=13/2

x=6 1/2

Mam nadzieje że dobrze

Szczegółowe wyjaśnienie:

Odpowiedź:

a) 8(2 x - 1) + 3(4 - 5x) =0

16x - 8 +12 - 15x +0

x+4=0

x= -4

b)2(7x - 3) = 5 - 4(6 - 4x)

14x - 6 = 5 - 24+16x

14x - 6x =  -19 +6

-2x= -13

x= [tex]\frac{13}{2}[/tex]

Szczegółowe wyjaśnienie: